Silicon supplied via foliar application and root to attenuate potassium deficiency in common bean plants - dos Santos Sarah, Marcilene Machado [UNESP]; de Mello Prado, Renato [UNESP]; de Souza Júnior, Jonas Pereira [UNESP]; Teixeira, Gelza Carliane Marques [UNESP]; dos Santos Duarte, João Carlos [UNESP]; de Medeiros, Robson Luis Silva [UNESP] (Springer Nature, 2021)
Potassium (K) deficiency affects physiological performance and decreases vegetative growth in common bean plants. Although silicon (Si) supplied via nutrient solution or foliar application may alleviate nutritional stress, research on the bean crop is incipient. Thus, two experiments were carried out: initially, a test was performed to determine the best source and foliar concentration of silicon. Subsequently, the chosen Si source was supplied in nutrient solution via roots or foliar application to verify whether Si supply forms are efficient in alleviating the effects of K deficiency. For these purposes, a completely randomized 2 × 3 factorial design was used, with two levels of K: deficient (0.2 mmol L−1 of K) and sufficient (6 mmol L−1 of K); and Si: in nutrient solution via roots (2 mmol L−1 of Si) or foliar application (5.4 mmol L−1 of Si) and control (0 mmol L−1 of Si). Our findings revealed that Si supplied via foliar spraying using the source of sodium silicate and stabilized potassium at a concentration of 5.4 mmol L−1 was agronomically viable for the cultivation of bean plant. K deficiency, when not supplied with silicon, compromised plant growth. Moreover, root-and-foliar-applied Si attenuated the effects of K deficiency as it increased chlorophylls and carotenoids content, photosynthetic activity, water use efficiency and vegetative growth. For the first time, the role of Si to mitigate K deficiency in the bean crop was evidenced, with a view to further research on plants that do not accumulate this beneficial element.